Miasto na ludzką miarę - Huckova, Jadwiga (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
The Human Scale The Danish director Andreas M. Dalsgaard’s film The Human Scale (2012) is discussed in the context of recent documentaries on similar subjects that have been shown at human rights festivals. The Human Scale is primarily an excellent lecture on the ideas of Danish architect and urban planner Jan Gehl. The cognitive tools of persuasion and artistic means were equilibrated and combined in the film in order to convince the viewer of the value of Gehl’s concepts.